Fibrinolytic System in Hypotensive Patients; with a Special Reference to the Effect of Epsilon-Amino Caproic Acid (EACA) - Gabryelewicz, A; Niewiarowski, S; Prokopowicz, J; Worowski, K (Thrombosis and Haemostasis, 1967)
An acceleration of euglobulin fibrinolysis and a slight decrease of plasminogen and of antiplasmin were found in idiopathic hypotensive patients. EACA administered orally in daily doses 0.1 g /kg of weight for 4 days produced both an inhibition of fibrinolysis and a significant rise in arterial blood pressure in 15 of 18 patients studied. It has been suggested that the pressure effect of EACA may be mediated by inhibiting plasminogen activation.